Development of new technologies for interlocking concrete block pavement (ICBP) - Md. Nor, Hasanan; Abd. Muti, Abd. Aziz; Che Puan, Othman; Chik, Abdul Aziz; Ismail, Che Ros; Ling, Tung Chai; Mudiyono, Rachmat (Faculty of Civil Engineering, 2008)
In concrete block pavements, the blocks make up the wearing surface and are a major load-spreading component of the pavement. This research investigate the anchor beam spacing of concrete block pavement (CBP) on sloping road section based on the degree of slope, laying pattern, blocks shape, blocks thickness, joint width between blocks and bedding sand thickness. The results of a series of tests conducted in laboratory with horizontal force test and push-in test in several degrees of slopes. The horizontal force testing installation was constructed within the steel frame 2.00 x 2.00 metre and forced from the side until CBP failure (maximum horizontal creep). For the applied push-in test in a rigid steel box of 1.00 x 1.00 metre square in plan and 0.20 meter depth, the vertical load was increased from zero to 51 kN on the CBP sample in 0%, 4%, 8% and 12% degrees of slopes. The herringbone 45o is the best laying pattern compared to herringbone 90o and stretcher bond to restraint the horizontal force, which the blocks contribute as a whole to the friction of the pavement, the blocks being successively locked by their rotation following their horizontal creep. The uni-pave block shape has more restraint of horizontal creep than rectangular block shape, because uni-pave block shape has gear (four-dents), while rectangular block shape has no gear (dents).The difference in deflections observed between uni-pave shape and rectangular shape are small. The change in block thickness from 60 to 100 mm significantly reduces the elastic deflection of pavement. The optimum joint width between blocks is 3 mm. For joint widths less than the optimum, the jointing sand was unable to enter between blocks. The relationship between push-in force with block displacement on the varying loose thicknesses of 30, 50, and 70 mm bedding sand, shows that the deflections of pavement increase with increase in loose thickness of bedding sand. The higher the loose bedding sand thickness, the more the deflection will be. The effect of the degree of slope on concrete block pavements on sloping road section area is significant with friction between blocks and thrusting action between adjacent blocks at hinging points is more effective with thicker blocks. Thus, deflections are much less for thicker blocks with increasing degree of the slope. The spacing of anchor beam is increase with decreasing joint width, degree of slope and bedding sand thickness. To compare results between laboratory test with the simulated mechanical behaviour of concrete block pavements, a structural model based on a Three Dimensional Finite Element Model (3DFEM) for CBP was employed. The concept of HALI development, including design, fabrication, calibration and performance monitoring is presented. Before HALI can be greatly introduced highway research institutions, the equipment was tested with 1 m x 5.4 m test pavement and subjected to 10,000 cycles of load repetition. Additional tests, including shear resistance, skid resistance, and impact resistance were also conducted in order to have a better understanding of the effects of the pavement behaviour tested under HALI.